The astrophysics of relativistic radio transients - Rhodes, L (2022)
Astrophysical jets are ubiquitously associated with the most energetic phenomema in the Universe. In this thesis, I will present and discuss radio observations of two types of transient systems: neutron star X-ray binaries and gamma-ray bursts (GRBs).